ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESULITAN BELAJAR MATEMATIKA KELAS 12 MAS TI BATANG KABUNG - Mandara, Aldian; Suherman, Suherman (Departemen Matematika, 2024)
This research aims to identify internal and external factors influencing the difficulty of learning mathematics in 12th-grade students. A qualitative research method was employed by collecting data through interviews and observations of students. The findings indicate that internal factors such as motivation, self-perception, and learning anxiety have a significant impact on the difficulty of learning mathematics. Meanwhile, external factors such as teaching quality, family support, and learning environment also contribute to the difficulty. Special attention is needed to build students' motivation and self-understanding, as well as to improve teaching methods and family support to enhance the quality of mathematics learning in the 12th grade.Keywords - Difficulty in learning mathematics, Teaching method improvement, Enhancement of mathematics learning quality